Kedudukan Alat Bukti Elektronik : Perkara Perceraian Di Pengadilan Agama Medan - Rahmadani, Gema; Irham, Muhammad Iqbal (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2024)
This article aims to analyze Electronic evidence which if printed and photocopied becomes evidence in the form of documents according to the Religious Court in the divorce process, which is written evidence, although other evidence is also considered important which is complementary to testimony. In the trial the parties may submit events that can be used as a basis for confirming their rights or to refute the rights of others. The kinds of evidence are: Writing, Witness, Testimony, Confession, Oath. The method used in this article is qualitative which is carried out by collecting, analyzing, and interpreting narratives comprehensively on visual data to obtain a complete and comprehensive insight into the proof of strong evidence in the Religious Court. The results of the study concluded that the strong evidence accepted by the judge is written evidence (documents), while some other evidence becomes supporting evidence in the trial process. Keywords: evidence, divorce, court